Safety valve or sinkhole? Vocational schooling in South Africa - Todd Pugatch (Institute for the Study of Labor (IZA), 2012)
As an alternative to traditional academic schooling, vocational schooling in South Africa may serve as a safety valve for students encountering difficulty in the transition from school to work. Yet if ineffective, vocational schooling could also be a sinkhole, offering little chance for success on the labor market. After defining the terms safety valve and sinkhole in a model of human capital investment with multiple schooling types, I test for evidence of these characteristics using a panel of urban youth in South Africa. I find support for the safety valve role of vocational schooling, with a small increase in vocational enrollment in response to grade failure, compared to a decline of 38 percentage points for academic enrollment. In contrast, I find no evidence that vocational schooling is a sinkhole, with wage and employment returns at least as large as those for academic schooling. The results suggest that vocational schooling plays an important role in easing difficult school to work transitions for South African youth.
Keywords: I25; J24; J31; O12; 330; human capital investment; vocational schooling; youth unemployment; South Africa